2014
DOI: 10.1016/j.ypmed.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Cultural relevance in medication adherence interventions with underrepresented adults: Systematic review and meta-analysis of outcomes

Abstract: Objective This meta-analysis systematically compiles intervention research designed to increase medication adherence among underrepresented adults. Method Comprehensive searching located published and unpublished studies with medication adherence behavior outcomes. Studies were included if samples were adults living in North America who had any of the following backgrounds or identities: African American, Native American, Latino, Latino American, Asian, Asian American, Pacific Islander, Native Alaskan, or Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
1
15
0
1
Order By: Relevance
“…Although the magnitude of the effect was relatively modest, it was nevertheless comparable to the effects found in previous meta-analyses of medication adherence interventions conducted in general populations ( d = 0.18–0.37). 64,65 Effects were also comparable to those found in meta-analysis of interventions directed at targeted populations of underrepresented racial/ethnic groups ( d = 0.211) 135 and older adults ( d = 0.33). 79 …”
Section: Discussionsupporting
confidence: 71%
“…Although the magnitude of the effect was relatively modest, it was nevertheless comparable to the effects found in previous meta-analyses of medication adherence interventions conducted in general populations ( d = 0.18–0.37). 64,65 Effects were also comparable to those found in meta-analysis of interventions directed at targeted populations of underrepresented racial/ethnic groups ( d = 0.211) 135 and older adults ( d = 0.33). 79 …”
Section: Discussionsupporting
confidence: 71%
“…The overall mean effect size of 0.300, which was calculated across 108 treatment vs. control comparisons, documents that treatment subjects had significantly better medication adherence outcomes than control subjects. This value was comparable to effect sizes reported in meta-analyses of adherence interventions conducted in general populations ( d = 0.18 to 0.37) [147, 148]; among older adults ( d = 0.33) [149]; adults with coronary artery disease ( d = 0.229) [150]; adults with heart failure ( d = 0.29) [151]; patients with adherence problems ( d = 0.301) [152]; and in targeted populations of underrepresented racial/ethnic groups ( d = 0.211) [153]. …”
Section: Discussionmentioning
confidence: 99%
“…2829–31 Using this same Kaiser diabetes registry, a previous study of ongoing medication adherence (employing other measures of adherence and models with different covariates) found that a combined lipid, blood pressure and diabetes medication adherence outcome varied by ethnicity of the patient and by the language capability of the providers, though diabetes medications alone did not. 28 Multiple explanations have been posited for greater non-adherence among Latinos, including issues of pharmacy logistics 32 , financial barriers 33 , numeracy and literacy barriers 34 , cultural attitudes toward medications 35 , and language barriers 36 . Latinos, particularly immigrants, also have high rates of depression, which may contribute to medication non-adherence.…”
Section: Discussionmentioning
confidence: 99%